SYNTHESIS AND CHARACTERIZATION OF PEROVSKITE OXIDES LAFE1-XCUXO3 (0 ≤ X ≤ 0.4) OBTAINED BY SOL-GEL METHOD - Benaicha, A.; Omari, M. (University of Eloued جامعة الوادي, 2018)
LaFe1-xCuxO3 (where x ranged from 0 to 0.4) powders are successfully prepared by the sol-gel method employing metal nitrate salts as cations precursors and methanol as solvent. Thermogravimetric and differential thermal analysis (TGA/DTA) results indicate that decomposition of the precursor to the oxide completed at about 750°C. XRD patterns exhibit that the materials belong to a cubic system. All samples show two IR active vibrational modes, one at 560 cm-1 assigned to Fe-O stretching vibration and another one at 1385 cm-1 due to the stretching of metal carbonates. SEM images of the samples show that the particle size is from 63 to 158 nm and the specific surface areas are relatively low. The electrochemical measurements indicate that the catalytic activity is influenced by copper doping. The highest electrode performance is achieved with the oxide LaFe0.7Cu0.3O3.
Artical in Journal of Fundamental and sciences. university of el oued
Keywords: perovskite oxide, sol-gel, thermogravimetric analysis, powder diffraction, electrochemical properties.